THE EFFICACY OF COMBINED PHARMACOLOGICAL BLOCKING OF RAAS IN CHILDREN WITH CHRONIC RENAL DISEASE - E.S. Otroshchenko; L.V. Leonova; O.V. Komarova; A.G. Timofeeva; A.N. Tsygin (Педиатрическая фармакология, 2010)
14 children with various clinical forms of steroid-resistant nephrotic syndrome have been examined to assess the efficacy of pharmacological blocking of RAAS using inhibitors of angiotensin-converting enzyme and Angiotensin II receptor blockers. While assessing the efficacy of the nephroprotective therapy, the following was found in all the children: a reliably meaningful 1,5 times reduction ((р = 0,013) in the daily proteinuria level in 3 to 6 months, and by the end of the study — a 2,5 times reduction (р = 0,001) and improvement in the renal filtration function metrics in 3 to 6 months (р = 0,001), in 1 year (р = 0,013) and by the end of the study (p = 0,002) in comparison with the metrics prior to the launch of the nephroprotective therapy. Key words: chronic renal disease, proteinuria, RAAS, angiotensin-converting enzyme inhibitors, angiotensin II receptor blockers. (Pediatric Pharmacology. – 2010; 7(2):105-109)